The Influence of Digital Technology with Application-based Interactive Multimedia Learning in Improving Junior High School students' English Vocabulary - Nurlela, Nurlela; Niswa, Khairun; Daulay, Sholihatul Hamidah (English Teaching and Linguistics Journal (ETLiJ), 2024)
The objective of this study is to ascertain the notable impact of utilizing the Busuu application on pupils' vocabulary. The Busuu program is an English language learning tool designed to enhance spelling, vocabulary, speaking skills, and word comprehension abilities.This study is conducted using experimental methods. The research samples consisted of an experimental class and a control class. The population for this study consists of eighth-grade students enrolled at SMP Muhammadiyah 57 Medan during the 2023/2024 academic year. The sampling method employed was purposive sampling. The test is multiple-choice. The research uses a vocabulary exam as its primary tool. The data, comprising 25 items, were analyzed using paired difference tests, specifically the Paired sample t-test, in SPSS version 27. The research findings indicate a disparity between the pre-test and post-test scores in the experimental class, with an average score of 65 and 76.54, respectively. Consequently, utilizing the Busuu program has resulted in a notable augmentation of kids' vocabulary. The analysis results indicate that the utilization of the Busuu application has a statistically significant value of 0.001, which is lower than the commonly accepted threshold of 0.05. This data suggests a substantial impact on the utilization of the Busuu application. Thus, the null hypothesis (H0) is refuted, and the alternative hypothesis (Ha) is affirmed.